Oncologists' Perceptions of a Digital Tool to Improve Cancer Survivors' Cardiovascular Health - Kelley, Marjorie; Foraker, Randi; Lin, En-Ju Deborah; Kulkarni, Manjusha; Lustberg, Maryam; Weaver, Kathryn E. (ACI Open, 2019)
Background Cardiovascular (CV) disease continues to be a leading cause of morbidity and mortality with higher rates among cancer survivors than in the general population.Objective This study was aimed to understand oncology providers' attitudes toward a digital CV health tool, delivered via a tablet, to promote CV health in cancer survivors.Methods Using qualitative methods, 14 oncologists, from community and academic practice sites, were interviewed while they used the tool. Interviews were videotaped then analyzed using NVivo 11 software. Themes were inductively developed from the interviews.Results Three major themes emerged from the interviews as follows: (1) system functionality, (2) facilitators and barriers to integration, and (3) appropriate end-users. Oncologists recognized the critical role of CV health promotion among cancer survivors and identified features about the tool that would be helpful for CV health promotion. Workflow (subtheme) was a barrier to tool use. This feedback enabled tool redesign for further testing in the context of survivorship care.Conclusion Our findings emphasized the importance of identifying appropriate End-users which may include other survivorship care providers, patients, and primary care providers.Implications Our research addresses the knowledge gap in the use of digital tools in cancer survivorship care, specifically digital tools to promote CV health. Future research is needed to evaluate digital tools in cancer survivorship care. Research investigating patients as users of digital tools may provide additional insight.
Keywords: cancer survivors; medical informatics; cardiovascular disease; lifestyle; patient participation